Exosomes as Targeted Delivery Platform of CRISPR/Cas9 for Therapeutic Genome Editing. (12th September 2021) - Duan, Li; Ouyang, Kan; Wang, Jianhong; Xu, Limei; Xu, Xiao; Wen, Caining; Xie, Yixin; Liang, Yujie; Xia, Jiang
Abstract: Therapeutic genome editing harnesses the power of genome editing tools to correct erroneous genes associated with disease pathology. To bring the CRISPR/Cas9 tool from the bench to the bedside, a critical hurdle is the safe and efficient delivery of this nucleic acid tool to the desired type of cells in patients. This review discusses the use of natural carriers, extracellular vesicles (EVs), in particular exosomes, to fill the gap. Exosomes are lipid‐containing nanovesicle released by various types of cells to mediate cell‐cell communications. Their inherent long‐distance transportation capability, biocompatibility, and engineerability have made EVs potential vehicles for delivering therapeutic drugs. We summarize the recent progress of harnessing exosomes as delivery vehicles for the CRISPR/Cas system to achieve therapeutic gene editing for disease treatment, with a focus on various strategies to achieve selective delivery to a particular type of cell and efficient packaging of the genome editing tools in the vesicles. Critical issues and possible solutions in the design and engineering of the targeting vehicles are highlighted. Taken together, we demonstrate EV/exosome‐mediated packaging of the nucleic acid/protein tools and the cell/tissue‐targeted delivery to be a viable way towards the clinical translation of the CRISPR/Cas9 technology. Abstract : Granting CRISPR/Cas9 molecules a protecting shield and a guiding "GPS", engineered exosomes enable genome editing selectively in targeted cells or tissues. These natural vehicles also encompass rich functional molecules which their synthetic counterparts do not have, making them an appealing tool for both basic research and translational medicine.